Makasusue as an Instrument of Customary Legitimacy: A Study on the Practice of Child Acknowledgment in the Soa Matoke Community - Sahetapy, Agustinus Jonas; Niapele, Sarifah (Faculty of Law, Universitas Pattimura, 2026)
Introduction: The issue of recognizing children born outside formal marital bonds remains a critical concern within indigenous communities, particularly when traditional values clash with the provisions of the state's positive legal system. In this context, the Soa Matoke indigenous community has developed its own mechanism known as makasusue, which serves as a means of resolution and social legitimization.Purposes of the Research: This study aims to examine and analyze the practice of makasusue as a customary instrument of legitimacy in the process of child recognition within the Soa Matoke community. The makasusue tradition holds a significant position in the social structure of the community, as it forms the basis for recognizing the identity and status of children born outside of formal marriage. This research seeks to explore how the makasusue mechanism is implemented, the customary values that underpin it, and its relevance to the principles of national law regarding child recognition.Methods of the Research: The research employs a qualitative approach. Data were collected through in-depth interviews with traditional leaders, soa heads, parents involved in the makasusue ritual, and other relevant parties, as well as participatory observation of makasusue practices in the field. The data are also supported by a review of customary documents and relevant regulations.Results Main Findings of the Research: The findings indicate that makasusue functions not only as a means of social reconciliation but also as a customary legal mechanism that provides social recognition and kinship rights to the child. This tradition represents a concrete manifestation of living law within indigenous society, although it continues to face challenges in its harmonization with Indonesia's positive legal system.